Efficacy and safety of adsorptive granulomonocytapheresis in Chinese patients with ulcerative colitis: A retrospective analysis of 50 cases with focus on factors impacting clinical efficacy. Issue 4 (7th May 2020) - Li, Na; Mao, Jingwei; Tang, Haiying; Zhu, Lei; Tan, Xiaoyan; Bi, Jian; Wu, Hao; Chen, Xiuli; Wang, Yingde
Abstract: Background: Myeloid‐derived leucocytes, a major source of inflammatory cytokines, play an important role in the exacerbation of ulcerative colitis (UC). Selective depletion of myeloid leucocytes by adsorptive granulomonocytapheresis (GMA) with an Adacolumn should alleviate inflammation and promote remission. However, there are discrepancies among the reported efficacy outcomes. This study aimed to evaluate the efficacy and safety of GMA in UC patients with a focus on factors affecting clinical efficacy. Methods: This was a retrospective analysis of 50 patients with active UC who had received GMA therapy. GMA efficacy was evaluated based on the Rachmilewitz's clinical activity index (CAI) and Mayo endoscopic score for mucosal healing. Laboratory findings were analyzed to demonstrate any relationship with the GMA‐responder or nonresponder feature. Adverse events were recorded during and after GMA therapy. Results: The overall clinical remission rate (CAI ≤4) was 79.2%, and among these, the mucosal healing rate was 59.2%. The clinical remission rate was 69.2% in patients who received 5 GMA sessions and 82.3% in patients who received 10 sessions. Significantly higher baseline CAIs and lower albumin and hemoglobin levels were observed in nonremission cases compared with those who achieved remission. Four patients (8%) experienced transient adverse events, but none were severe. Conclusions: GMA was favored by patients because of its safety and nonpharmacological treatment options. Accordingly, UC patients were spared from pharmaceuticals after applying GMA therapy.